Probiotics and Its Effects on the Cognitive Development in Children: A Meta-Analysis - Ambarsari, Anggraini; Murti, Bhisma; Rahardjo, Setyo Sri (Indonesian Journal of Medicine, 2022)
Background: Due to its high morbidity and mortality rate, diarrhea is still a major health problem among children, particularly toddlers, in developing countries. One of the causes of diarrhea in children is the side effect of antibiotics or known as antibiotic-associated diarrhea (AAD). Evidences of studies conducted in several countries indicated the high use of antibiotics among children that put the group at a high risk of enduring AAD. Probiotics has shown efficacy in preventing and curing various medical conditions, especially those involving digestive tract in children.Subject and Method: It was a systematic review and meta- analisis study. Data collection was conducted by obtaining from databases, namely: Google Scholar, PubMed, Scopus and Science Direct. The study was analyzed by using RevMan 5.3 software. Inclusion criteria used were full paper in English with Randomized controlled trial design during the period of 2000-2022. Keywords used were “Probiotic” AND “Antibiotic Associated Antibiotic” AND “Child” AND “Randomized Controlled Trial”.Results: Meta-analisis was conducted to 9 primary studies from several countries such as Poland, Italy, Korea, Iran, and Australia. Mata-analysis concludes that there were effects of probiotics toward antibiotic-associated diarrhea. Children who were given probiotics had one-third time risk of diarrhea episodes compared to those who were not given probiotics (RR= 0.32; 95% CI= 0.23 to 0.44; p<0.001). Heterogeneity of between-study effect estimates of the meta-analysis data was (I2= 0%; p= 0.096) therefore, calculation of effect estimates was written by using fixed effect approach. Funnel plot did not identify the occurrence of publication bias out of the meta-analysis. Therefore, the funnel plot did not identify the occurrence of publication bias.Conclusion: Probiotics have effects in reducing antibiotics-associated diarrhea incidences in children.Keywords: probiotics, diarrhea, antibiotics.Correspondence:Anggraini Ambarsari. Masters Program in Public Health, Sebelas Maret University. Jalan Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: Aanggraini.ambarsari29@gmail.com. Mobile: 085600184363Indonesian Journal of Medicine (2022), 07(02): 232-241https://doi.org/10.26911/theijmed.2022.07.02.11